(untitled) (International Seven Journal of Multidisciplinary, 2024)
This article addresses the benefits of physical activity in improving the physical fitness of the elderly. Regular exercise is effective in increasing muscle strength, improving cardiovascular endurance, preventing chronic diseases, and improving psychological well-being. In addition, it highlights the importance of personalized and supervised exercise programs to maximize the benefits of physical activity in healthy aging.